Left‐Handed Materials: Three‐Dimensional Super Lens Composed of Fractal Left‐Handed Materials (Advanced Optical Materials 7/2013). Issue 7 (25th July 2013) - Xu, He‐Xiu; Wang, Guang‐Ming; Qi, Mei Qing; Li, Lianming; Cui, Tie Jun
<x xml:space="preserve">Abstract</x> A 3D super lens composed of fractal left‐handed materials is realized by H.‐X. Xu, T. J. Cui, and co‐workers. By incorporating four interdigital capacitors in the Sierpinski fractal curves of the second iteration order, the left‐handed transmission‐line material facilitates an electrically small dimension and a broadband negative magnetic response. Based on such metamaterials, a planar slab super lens is designed and fabricated on page 495. Both numerical and experimental results illustrate that the superlens exhibits excellent impedance matching to free space and significantly improves the imaging resolution. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>